Vernacular architecture and regional design : cultural process and environmental response - Heath, Kingston Wm. (Boston, MS : Elsevier Ltd, 2009)
Defines a set of strategies for understanding the complexities of a regional setting and, through a series of international case studies, examines how architects and designers have applied a variety of tactics to achieve culturally and environmentally appropriate design solutions.
asection 1. Exploring the nature of place -- section 2. From regional theory to a situated regional response -- pt. 1. People : improving the human condition through design -- pt. 2. Locale : interpreting and accommodating characteristics of an evolving landscape -- pt. 3. Environment : appropriate technologies and design tied to the dynamics of place.
Includes index.
engineering bookfair2015
Keywords: Vernacular architecture; Sustainable architecture